2014
DOI: 10.1371/journal.pone.0089827
|View full text |Cite
|
Sign up to set email alerts
|

Altered Lipid Levels in Untreated Patients with Early Polymyositis

Abstract: BackgroundLittle is known so far on the lipid profile in polymyositis (PM) patients. Our aim is to identify lipid profiles in untreated patients with early PM, to assess the association between lipid profiles and C-reactive protein (a sensitive marker of inflammation) in these patients.Methods and FindingsThis work was conducted as a case-control study. Sixty untreated patients with PM and 60 age- and sex-matched healthy controls were included. The duration of PM was less than six months, and none of them had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For example, the study by Antovic et al (26) and the study by Moshtaghi-Svensson et al (27) used the same databases (the Swedish National Patient Register Database and the Swedish Population Register Database), but the latter reported the most comprehensive results, thus, we only included the study by Moshtaghi-Svensson et al in the current review. Finally, seven articles focused on CHD risk and nine articles focused on cardiovascular risk factors met the inclusion criteria and were included in this meta-analysis (11)(12)(13)(14)(15)(16)(17)(27)(28)(29)(30)(31)(32)(33)(34). Moreover, the majority of eligible studies in the current review were about patients with DM/PM, but these studies did not describe the different subtypes of PM or DM in detail.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the study by Antovic et al (26) and the study by Moshtaghi-Svensson et al (27) used the same databases (the Swedish National Patient Register Database and the Swedish Population Register Database), but the latter reported the most comprehensive results, thus, we only included the study by Moshtaghi-Svensson et al in the current review. Finally, seven articles focused on CHD risk and nine articles focused on cardiovascular risk factors met the inclusion criteria and were included in this meta-analysis (11)(12)(13)(14)(15)(16)(17)(27)(28)(29)(30)(31)(32)(33)(34). Moreover, the majority of eligible studies in the current review were about patients with DM/PM, but these studies did not describe the different subtypes of PM or DM in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence suggests that traditional CV risk factors (including diabetes, hypertension, dyslipidaemia, obesity and smoking) are more prevalent in adult onset IIM than in the general population ( table 1 ); this has especially been found for abdominal obesity. 22 36 37 Increased prevalence of hypertension and dyslipidaemia has also been shown in untreated patients with IIM, 38 39 which indicates an effect of the disease per se in addition to a possible effect of long-term glucocorticoid treatment. Also in JDM, hypertension and dyslipidaemia have been demonstrated ( table 1 ).…”
Section: Traditional Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Different mechanisms are suspected in the development of cardiac involvement in IIM. Recently, Wang et al found dyslipidaemia in newly diagnosed, untreated patients with PM 39 and with DM, 38 with lower high-density lipoprotein cholesterol (HDL-c) and higher triglycerides and total-/HDL cholesterol (TC/HDL) ratio than matched controls. High TC/HDL ratio is a predictor of ischaemic heart disease, superior to other lipid parameters such as TC and HDL/low-density lipoprotein (LDL).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Information on lipid profiles in patients with PM or DM is very limited. A few reports suggest altered serum levels of low-density lipoprotein (LDL)-cholesterol, high-density lipoprotein (HDL)-cholesterol, total cholesterol and triglycerides indicating changes in lipid metabolism in these diseases [ 24 – 26 ]. The dyslipidemia was associated with disease activity in one study and may reflect an interaction between inflammation and lipid metabolism [ 26 ].…”
Section: Introductionmentioning
confidence: 99%